Bibliometric Analysis: Technology Research in Adult Learning Using Vosviewer on Google Scholar - Vevi Sunarti; Jamaris Jamaris; Wisroni Wisroni; Jalius Jalius; Rembulan Catra Banyu Biru; Zaiful Netra; Shahid Rasool (Universitas Negeri Padang, 2024)
This study aims to understand the development of research on technology in the context of adult learning over the last ten years. This study used bibliometric analysis to identify research trends, relationships between concepts, and author collaborations. The data is obtained from the Google Scholar database with relevant keywords, and the number of publications is limited to 1,000 journals. The results show fluctuations in the growth of publications about technology in the context of adult learning from 2014 to 2023. Out of 1,000 publications indexed by Google Scholar, only 628 have information on year and publisher, while 308 do not. The peak of publication growth occurred in 2021, with 105 publications (16.7%), while the lowest number of publications was recorded in 2017, with 50 documents (8%). Research shows that the use of technology in adult learning continues to evolve. Nonetheless, there is still a paucity of research on technology and knowledge of andragogical content in adult learning. This provides an opportunity for other researchers to continue to develop this research trend.